Influências da Remuneração de Executivos na Congruência de Metas - José Carlos Tiomatsu Oyadomari (Revista Contemporânea de Contabilidade, 2009)
This study has the aim of identifying which variable remuneration practices are being used by the companies and how the remuneration goals are linked to the goals derived of the Management Control System and also, if there is coherence between the individual and organizational goals. The study was developed within 21 big companies, the majority part of the ranking of the biggest 200 economical groups, ranked by "Valor conômico". The obtained results show: 1) the variable remuneration, with individual goals, is linked to reaching the organizational goals; 2) the adopted practices by the market for the variable remuneration has a different power talking about the managerial behavior; 3) the action confl ict can be shown if the individual goals have not associated to the global goals of the organization; 4) the variable remuneration system has a motivating in the search of the a performance.